South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper highlights that aided by the easing of political uncertainties after the national elections in early 1994 and by the cautious stance of policies adopted by the new administration, economic performance and investor sentiment in South Africa strengthened markedly. Nonagricultural value-added grew by 4 percent in 1995, led by a sharp increase in real gross private fixed investment. In contrast, developments in 1996 were characterized by a shift in investor sentiment and unrest in the foreign exchange markets.